Clinical impact of rapid influenza PCR in the adult emergency department on patient management, ED length of stay, and nosocomial infection rate. Issue 2 (26th August 2020) - Peaper, David R.; Branson, Brittany; Parwani, Vivek; Ulrich, Andrew; Shapiro, Marc J.; Clemons, Crystal; Campbell, Melissa; Owen, Maureen; Martinello, Richard A.; Landry, Marie L.
Abstract: Background: Seasonal influenza causes significant morbidity and mortality and incurs large economic costs. Influenza like illness is a common presenting concern to Emergency Departments (ED), and optimizing the diagnosis of influenza in the ED has the potential to positively affect patient management and outcomes. Therapeutic guidelines have been established to identify which patients most likely will benefit from anti‐viral therapy. Objectives: We assessed the impact of rapid influenza PCR testing of ED patients on laboratory result generation and patient management across two influenza seasons. Methods: A pre‐post study was performed following a multifaceted clinical redesign including the implementation of rapid influenza PCR at three diverse EDs comparing the 2016‐2017 and 2017‐2018 influenza seasons. Testing parameters including turn‐around‐time and diagnostic efficiency were measured along with rates of bed transfers, hospital‐acquired (HA) influenza, and ED length of stay (LOS). Results: More testing of discharged patients was performed in the post‐intervention period, but influenza rates were the same. Identification of influenza‐positive patients was significantly faster, and there was faster and more appropriate prescription of anti‐influenza medication. There were no differences in bed transfer rates or HA influenza, but ED LOS was reduced by 74 minutes following clinical redesign. Conclusions: Multifaceted clinical redesign to optimize ED workflow incorporating rapid influenza PCR testing can be successfully deployed across different ED environments. Adoption of rapid influenza PCR can streamline testing and improve antiviral stewardship and ED workflow including reducing LOS. Further study is needed to determine if other outcomes including bed transfers and rates of HA influenza can be affected by improved testing practices.